Developing a mealybug pheromone monitoring tool to enhance IPM practices in New Zealand vineyards - Sullivan, Nicola J.; Bell, Vaughn A.; Butler, Ruth C.; Wallis, Roger; Ramesh, Remya; Reddy, D. Srinivasa; Twidle, Andrew M.; Bunn, Barry; Unelius, C. Rikard; Manning, Lee-Anne M.; Suckling, David M. (Journal of Pest Science, 2023)
Mealybugs are phloem-feeding insects found on many crops worldwide. In New Zealand vineyards, they transmit the economically important Grapevine leafroll-associated virus 3 (GLRaV-3). For some mealybug species, synthetic sex pheromones have been commercialised, and are used as monitoring tools. The mealybugs Pseudococcus longispinus and Pseudococcus calceolariae are major pests in many New Zealand vineyards. We present work on the development of a combined P. longispinus and P. calceolariae pheromone lure. The optimal dose for monitoring P. longispinus was found to be 10 mu g of the (S)-(+)-enantiomer, either alone or in the racemic mixture. Addition of the corresponding alcohol did not improve trap catch of P. longispinus. Both the P. longispinus and the P. calceolariae pheromone lures remained active in the field for 90 days. Combining the 2 species' pheromones had no negative effects on male mealybug trap catch for either species. We conclude that the pheromone ester alone is the best lure for the male P. longispinus. Combining the two mealybug species' pheromones into a single lure provides the New Zealand viticultural industry with an efficient monitoring tool. Late-vintage deployment of baited lures will provide information on mealybug abundance and local distribution that will inform the scope of future insecticide programmes, to target areas based on need rather than an area-wide application by default.
Keywords: Citrophilus mealybug; Integrated pest management (IPM); Long-tailed mealybug; monitoring; Pseudococcus calceolariae; Pseudococcus longispinus